Hepatic venous pressure gradient measurement guiding nonselective beta‐blocker therapy in a patient with clinically significant portal hypertension - Wang, Kun; Tian, Minghui; Zhang, Linpeng; Liu, Shanghao; Guo, Xiaoqing; Ma, Jianzhong (Portal hypertension & cirrhosis (Print), 2023)
Clinically significant portal hypertension (CSPH), defined as a hepatic venous pressure gradient (HVPG) ≥ 10 mmHg, is an independent risk factor for decompensated events in patients with compensated cirrhosis. Currently, the Baveno VII consensus recommends using nonselective beta‐blockers to treat compensated cirrhosis in patients with CSPH. Here, we report a unusual case of compensated cirrhosis with CSPH caused by hepatitis B, and we successfully adjust NSBBs drug treatment strategies monitoring by HVPG results and achieve response standards. Timely adjustment of NSBBs drug treatment strategies based on HVPG test results for patients with CSPH can improve the final response rate. Key points Timely adjustment of NSBBs drug treatment strategies for patients with CSPH based on HVPG test results can improve the final response rate. What this study adds? Early screening, diagnosis, and treatment can be achieved to ultimately improve the prognosis of patients with CSPH cirrhosis.